The Impact of climatic fluctuations in the production of citrus in the province of Karbala - د.طھ رؤوف شیر محمد نجلاء صباح مھدي السامرائي (College of Education for Women, 2019)
The relationship between the elements of the climate and the productivity of citrus (kg / tree) in the province of Karbala has been determined through the use of simple correlation coefficient of Pearson (rp) and (t) test. The result for each of oranges, limes and tangerine had all shown moral and relevant statistical indications; except for relative humidity, which were not linked to a moral relationship with productivity of tangerine, oranges and limes.As for the relationship between climatic factors and yield of bitter orange were all not significant statistically and very weak. In order to determine the strength of the correlation between fluctuations in the climatic elements and fluctuations in the productivity of citrus, the researcher has resorted to measure the "regression coefficient" (b) between the two variables. The value of (b) calculated for the relationship between fluctuations in hours of sunshine, maximum temperatures, minimum temperatures and wind speed, compared to the fluctuations in the productivity